Platelet derived growth factor BB: a “must-have” therapeutic target “redivivus” in ovarian cancer - Cimpean, Anca Maria; Cobec, Ionut Marcel; Ceaușu, Raluca Amalia; Popescu, Roxana; Tudor, Anca; Raica, Marius (Cancer genomics & proteomics, 2016)
Background: We aimed to validate PDGF-BB protein expression by RNAscope, a sensitive method for PDGF-BB mRNA evaluation on paraffin embedded (FFPE) specimens of ovarian tumors. Materials and Methods: Seventy-five FFPE ovarian cancer biopsies were assessed by immunohistochemistry followed by PDGF-BB mRNA RNAscope validation. Results and Conclusion: Dual PDGF-BB expression in tumor and stromal cells have been observed, being highly suggestive for PDGF-BB mediated stromal-tumor cells reciprocal interaction in ovarian cancer (p=0.008). It seems that the nuclear expression of the PDGF-BB represents a negative prognostic factor in ovarian tumors. Being a controversial issue in the literature, PDGF-BB nuclear expression detected by immunohistochemistry was validated by RNAscope in situ hybridization. More than 65% of cases had PDGF-BB mRNA amplification, confirming immunohistochemical results. We herein validated PDGF-BB as a potential therapeutic and prognostic tool of ovarian cancer aggressiveness.